The Influence of Social Class, Lifestyle, and Personality on Buying Decisions at the Car Showroom in Denpasar - Widi Antara, I Kadek Dwi; Diah Savitri, Ni Made Hary; Pramana Putra, I Wayan Anggi; Kadek Cahyana, Gusti Ayu; Windi Sasmita, Ni Kadek; Mitariani, Ni Wayan Eka; Yudhi Hendrawan, I Gede (Journal of International Conference Proceedings, 2024)
Along with the increasing number of car users which shows the development of lifestyles among people in Indonesia, many consumers who have owned a car before wish to sell their old car or exchange it for a new car, thus generating used cars that are still worth selling and providing opportunities for used car showroom business actors. The purpose of this study was to analyze the influence of social class, lifestyle, and personality on purchasing decisions for used Toyota cars at the Dharma Mahendra Mobilindo showroom in Denpasar. The data analysis technique uses multiple linear regression using the SPSS for Windows version 25 program. The results of the analysis in this study show (1) Social class has a positive and significant effect on purchasing decisions for used Toyota cars at DMM showrooms, (2) Lifestyle has a positive and significant effect on purchasing decisions for used Toyota cars at DMM showrooms, (3) Personality has a positive and significant effect on purchasing decisions for used Toyota cars at DMM showrooms. These findings suggest that businesses should focus on segmenting their marketing efforts based on social class, lifestyle preferences, and personality traits to better appeal to their target audience and optimize sales strategies